Applications of Vitrinite Anisotropy in the Tectonics: A Case Study of Huaibei Coalfield, Southern North China. (23rd August 2012) - Wu, Yudong; Hou, Quanlin; Ju, Yiwen; Cao, Daiyong; Fan, Junjia; Wei, Wei
Abstract : 29 oriented and 10 nonoriented coal samples are collected in the study from three different regions of the Huaibei coalfield, eastern China, and their vitrinite reflectance indicating surface (RIS) parameters are systematically calculated and analyzed. Using the available methods, Kilby's transformations and RIS triaxial orientations are obtained. The magnitudes and orientations of the RIS axes of the three regions were respectively projected on the horizontal planes and vertical sections. The results show that the samples in high deformed region have significant anisotropy magnitudes (higherB w / R max andR am values) with a biaxial negative style, whereas the samples in the slightly deformed area have unimpressive anisotropy magnitudes with a biaxial negative style. Thermal metamorphism superposed might enhance the complication and variation of RIS style. RIS projection analysis deduced that the RIS orientation is mainly controlled by regional tectonic stress, and likely influenced by deformation mechanisms of coal.